The Design of a Public Relations Services Information System for Creative Media State Polytechnic Using the Agile Development Method - Yuliana, Citra Ayu; Kartika, Tipri Rose; Mawardi, Cholid (International Journal of Computer and Information System (IJCIS), 2025)
Vocational colleges play a crucial role in producing a work-ready human resource with skills that align with industry demands through practice-based learning and direct application. In this context, effective communication between vocational colleges and prospective students becomes a critical aspect. One form of this communication is introducing vocational education through promotional and outreach activities conducted by the Polimedia Public Relations (Humas) department. The "Polimedia Open House" and "Polimedia Goes to School" are two main programs organized by Humas Polimedia, aiming to introduce the campus to prospective students and provide an overview of the educational system and facilities available. This research aims to design and develop an information system for registering for Public Relations services, specifically the Polimedia Open House and Polimedia Goes to School events. The system was built using the Laravel framework, applying the Software Development Life Cycle (SDLC) method with an Agile Development Cycle approach for subsequent implementation by schools wishing to visit Polimedia. The system development was conducted iteratively through the stages of planning, requirements gathering, design, development and testing, implementation, and review. This web-based information system was created using the PHP programming language and a MySQL database. The system is equipped with registration features for the Polimedia Open House and Polimedia Goes to School activities, a gallery of event documentation, registration status tracking, and contact information. With this system, it is expected to simplify the management of event information for the Public Relations department and attract more schools to visit.